Processing of Positive Visual Stimuli Before and After Symptoms Provocation in Posttraumatic Stress Disorder – A Functional Magnetic Resonance Imaging Study of Trauma-Affected Male Refugees. (April 2020) - Uldall, Sigurd W.; Madsen, Kristoffer H.; Siebner, Hartwig R.; Lanius, Ruth; Frewen, Paul; Fischer, Elvira; Madsen, Camilla G.; Leffers, Anne-Mette; Rostrup, Egill; Carlsson, Jessica L.; Nejad, Ayna B.
Background: Symptoms of anhedonia are often central to posttraumatic stress disorder (PTSD), but it is unclear how anhedonia is affected by processes induced by reliving past traumatic memories. Methods: Sixty-nine male refugees (PTSD = 38) were interviewed and scanned with functional magnetic resonance imaging while viewing positive, neutral and Scrambled Pictures after being read personalized scripts evoking an emotionally neutral memory and a traumatic memory. We further measured postprovocation state symptoms, physiological measures and PTSD symptoms. We tested whether neural activity associated with positive picture viewing in participants with PTSD was differentially affected by symptom provocation compared to controls. Results: For the pictures > scrambled contrast (Positive contrast), PTSD participants had significantly less activity than controls in fusiform gyrus, right inferior temporal gyrus and left middle occipital gyrus. The Positive contrast activity in fusiform gyrus scaled negatively with anhedonia symptoms in PTSD participants after controlling for total PTSD severity. Relative to the emotionally Neutral Script, the Trauma Script decreased positive picture viewing activity in posterior cingulate cortex, precuneus and left calcarine gyrus, but there was no difference between PTSD participants and controls. Conclusions: We found reduced responsiveness of higher visual processing of emotionally positive pictures in PTSD. The significant correlation found between positive picture viewing activity and anhedonia suggests the reduced responsiveness to be due to the severity of anhedonia.